Reconstruction of Hamka's Neo-Sufism in the Contemporary Era: Synthesis of Tradition and Modernity - Ismawati Saragih; Amroeni Drajat; Elly Warnisah Harahap (World Journal of Islamic Learning and Teaching, 2024)
This research aims to examine Hamka's views on neo-Sufism and understand how he views this phenomenon from a religious, social and intellectual perspective. Hamka, as one of the Islamic reformers in Indonesia, tried to harmonize the exoteric (natali) and esoteric (batini) aspects in his teachings. He offers a concept of Sufism that prioritizes cleanliness of the heart and seeks to synergize social and spiritual elements. This research uses a qualitative research design with a content analysis method. The data analyzed includes descriptions and opinions from books written by Hamka as well as discussions of thoughts written by them and others. Through this analysis, the researcher seeks to understand the complexity of the relationship between religious traditions and the challenges of modernity in Hamka's view of neo-Sufism. The results of the research show that Hamka criticizes certain aspects of neo-Sufism which he considers to be contrary to true Islamic teachings, such as mystical practices that have no basis in the Koran and Sunnah, as well as excessive emphasis on spiritual experiences without being based on solid religious knowledge. Hamka emphasized the importance of knowledge, education and spiritual guidance in achieving a correct understanding of Islam and the practice of Sufism in accordance with Islamic values. Hamka's views on neo-Sufism also reflect his concern about the social and cultural changes of his time. He offers active, dynamic and progressive Sufism as a solution to the spiritual crisis of modern humans. Hamka emphasized the need for stronger and more dynamic involvement in society, as well as maintaining a balance between worldly life and the afterlife. This research provides insight into the complexity of the relationship between religious traditions and the challenges of modernity within the framework of Hamka's thinking, as well as the importance of maintaining the integrity of Islamic teachings in facing the dynamics of changing times. The study of Hamka's views on neo-Sufism provides an important basis for understanding the religious and intellectual dynamics in contemporary Islam.